In Vitro Activities of Sparfloxacin, Ceftriaxone, Penicillin, Tetracycline and Doxycycline against Chlamydia trachomatis and Neisseria gonhorrhoeae. (1st June 1992) - Talbot, Hazel; Romanowski, Barbara
Abstract : In vitro sparfloxacin was highly active against 223 penicillin-susceptible isolates of Neisseria gonorrhoeae with a 90% minimal inhibitory concentration (MIC90 ) of 0.004 μg/mL. Resistant strains of N gonorrhoeae totalled 55; 32 were penicillinase-producing and 23 chromosomally resistant. The MIC90 for these isolates was 0.004 μg/mL and 0.008 μg/mL, respectively. Chlamydia trachomatis was also very susceptible with an MIC50 of 0.063 μg/mL and a 50% minimal bactericidal concentration of 0.032 μg/mL for 11 isolates.